KONTRIBUSI PENGALAMAN PRAKTEK KERJA INDUSTRITERHADAP KESIAPAN KERJA SISWA JURUSAN TEKNIK BANGUNAN SMK NEGERI 1 PADANG - 2033-2040, Azis Rifai (CIVED, 2018)
This study was to reveal how much the industrial work experience to the readiness of  working class XII students  majoring  in  building  engineering  at  SMK  Negeri  1  Padang.This  type  of  research  is  quantitative  with correlational descriptive approach. The sample in this research is 116 students using total sampling Research instrument used in the form of  questionnaire with Likert scale. The research trials was conducted on 30 students of class XII of SMK Negeri 5 Padang, the reason to test of  instrument at SMKN 5 Padang because (1) It is impossible to get the experiment in SMKN 1 Padang due to the limited number of samples and population, (2) SMKN 5 Padang the same characteristics as SMKN 1 Padang. Data analysis techniques used are descriptive analysis, test data analysis requirements and  hypothesis testing.The results of the study revealed that there positive correlation at the variabel  experience of industrial work practices to the readiness of students' work of the students of class XII SMKN 1 Padang 2017/2018.The effective contribution of technical internship experience amounted to 41.73% and the amount of other contributions was found to be another factor. Keywords: experience, industrial practice, working readiness